Coplanar Waveguide-Fed Broadband Microwave Devices with (or without) a Thin Dielectric Substrate for Use in Flexible Electronic Systems - Rafal Lech; Wojciech Marynowski; Adam Kusiek; Jerzy Mazur (International Journal of Antennas and Propagation)
Two examples of microwave devices, fed by a coplanar waveguide and realized on a thin substrate (or without such a substrate), are employed to investigate the influence of devices’ curvatures and the proximity of different materials on their parameters. To perform the tests, a broadband antenna and a low-pass filter are chosen. A feeding coplanar waveguide is realized on a dielectric material brick attached to an SMA connector and the main device structure is placed in the air or on a thin substrate. The utilization of a thin substrate or its removal from the structure gives rise to the possibility of placing the devices on curved surfaces. The investigated devices are redesigned and manufactured. The antenna has a total size of 46 mm × 44 mm and covers a frequency range of 2.4–35 GHz which gives a 174% fractional bandwidth. The filter has a total size of 50 mm × 80 mm and its bandwidth has a cutoff frequency of 3.4 GHz. The obtained results are verified by measurements and good agreement is achieved.